Chance events and strategic competitive advantage in elite sport: crises and sport-specific chance events - Zheng, J.; Tan, T. C.; Jiang, R. S. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
More women are successfully combining their elite athletic careers with motherhood, however for many, pregnancy and motherhood are often one of the main reasons they end their sporting careers. While there has been some focus in recent years regarding this topic, there are limited reviews of the literature regarding the experiences of elite athletes with pregnancy and motherhood. Adopting a Scoping Review approach, we reviewed 40 studies exploring motherhood and elite sport. Overall, the studies analysed for this scoping review provide a mixed picture of the biomedical and social aspects related to female elite athletes and pregnancy. The bio-medically focused studies tended to adopt a quantitative or mixed-method perspective with a predom inant focus on physical changes, injuries, and performance outcomes, whilst reviewed qualitative studies focused on a variety of social factors that can impact a female athlete`s return to elite sport including child care and access to maternity leave.